KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK PADA BERBAGAI PROPORSI TAPIOKA DAN TEPUNG KACANG HIJAU - Linardi, Gracia Fransisca; Kuswardani, Indah; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2013)
Crackers is a popular food in Indonesia. Public appetite for eating crackers continues to increase, so diversification of crackers need to be develop with diversification crackers from mung bean.The purpose of this research is to determine the effect of the proportion between tapioca and mung bean flour on physicochemical and organoleptic properties of mung bean cracker and get the best treatment combination. The materials for mung bean cracker is tapioca and mung bean flour. The different proportion of tapioca and mung bean flour can be affect physicochemical and organoleptic properties of cracker. The design of the study is a single randomized group design, spesifically proportion of tapioca and mung bean flour which consists of six levels and was repeated four times, 9:1, 8:2, 7:3, 6:4, 5:5, and 4:6. The results showed significantly affect the water content of raw and fried crackers, expansion volume, oil absorbtion, fracture, crispness, and organoleptic (taste, color, crispness). The higher proportion of mung bean flour, the lower the moisture content of raw crackers, expansion volume, oil absorption, crispness, and the higher hardness, water content of fried crackers. The best treatment based on organoleptic properties is crackers with proportion of tapioca : mung bean flour at 8:2 (T8H2).